Do household definitions matter in survey design? Results from a randomized survey experiment in Mali - Beaman, Lori; Dillon, Andrew (International Food Policy Research Institute, 2010)
Household definitions used in multi-topic household surveys vary between surveys but have potentially significant implications for household composition, production, and poverty statistics. Standard definitions of the household usually include some intersection of keywords relating to residency requirements, common food consumption, and intermingling of income or production decisions. Despite best practices intending to standardize the definition of the household, it is unclear which types of definitions or which intersections of keywords in a definition result in different household compositions. This paper conducts a randomized survey experiment of four different household definitions in Mali to examine the implications for household-level statistics. This approach permits analysis of the trade-offs between alternative definition types. We find that additional keywords in definitions increase rather than decrease household size and significantly alter household composition. Definitions emphasizing common consumption or joint production increase estimates of the levels of household assets and consumption statistics, but not on per adult equivalency asset and consumption statistics, relative to open-ended definitions of the household. In contrast, definition type did not affect production statistics in levels, although we observe significant differences in per adult equivalency terms. Our findings suggest that variations in household definition have implications for measuring household welfare and production over time and across countries, as well as evaluation studies where the correct measure of spillover effects within and across households is necessary for measuring the benefits of an intervention.